Phased-resolved partial discharge patterns of 10 kV stator coils under different experimental conditions. (September 2020) - Kang, Ailiang; Tian, Muqin; Lin, Lingyan; Song, Jiancheng; Li, Wei; Li, Lu
Abstract: The most five common types of partial discharge (PD) activities involving 10 kV motors, namely internal discharge, slot discharge, corona discharge, surface tracking and bar-to-bar discharge, were researched in this paper. PD was induced on some 10 kV coils with modern epoxy-mica insulation system through off-line experiment under different conditions. The phased-resolved partial discharge (PRPD) patterns of different types of PDs were recorded to characterize different PDs. This research can provide a reference in off-line fault diagnosis and be useful for the PD online monitoring of high voltage motors.